P004 Addition of an oral expiratory positive pressure valve (EPAP) to an oral appliance therapy device can resolve obstructive sleep aponea (OSA). (9th November 2022) - Aishah, A; Osman, A; Tong, B; Pitcher, G; Eckert, D; Mukherjee, S
Abstract: Background: Mandibular advancement splints (MAS) provide effective therapy for many people with OSA. However, in ~50% of cases, MAS alone does not fully resolve OSA. A single-night study showed that ~45% of people with incompletely treated OSA with MAS alone had resolution (apnoea-hypopnea index [AHI]<10 events/h) with the addition of an oral expiratory positive airway pressure (EPAP) valve. This study aimed to determine the safety, tolerability, and longer-term efficacy of oral EPAP valve plus MAS in incomplete responders to MAS alone. Methods: Seven people with OSA (AHI=26±13events/h) not fully resolved with MAS alone (AHI>10events/h) were recruited. In-laboratory polysomnography with MAS plus oral EPAP was performed on night 1. Participants then used MAS+EPAP at home for 30-days and completed weekly questionnaires to assess safety, tolerability, and next-morning sleepiness (Karolinska sleepiness scale, KSS). Impact on daytime sleepiness (Epworth sleepiness scale, ESS) was assessed at night 1 and 30. A final at-home WatchPAT study was performed at night 30. Results: OSA was successfully treated (AHI<10events/h) in 4/7 participants during the night 1 in-laboratory study (MAS alone vs. MAS+ EPAP: 13±2 vs. 7±2events/h). Five had treatment success by night 30 (6±3events/h). Daytime sleepiness (ESS) did not change after 30 days of MAS+EPAP although next-morning sleepiness tended to reduce ( KSS: 4.4±1.9 vs. 3.3±1.5, p=0.047 n=7). Oral EPAP was generally well-tolerated with no major side effects reported. Discussion: Oral EPAP may be an effective treatment addition for some people with OSA who have an incomplete therapeutic response to MAS alone.